STUDENT LEARNING OUTCOMES ON OPPORTUNITY MATERIALS IN CLASS XII MTS MA AL ITTIHADIYAH MEDAN JOHOR - Nurdalilah, Nurdalilah; Rindiani, Rizki; Wahyuni, Sri Devi; Ratamina, Shally; Zakiah, Putri; Hati, Suci (Nindikayla Institute, 2024)
Opportunity is one of the materials studied in Mathematics and is important to study because it has many contributions both in advanced mathematics material and in everyday life. However, in reality, many students have difficulties in applying opportunity material to advanced material and in everyday life. Therefore, researchers conducted research that aims to 1) Describe student learning outcomes in opportunity material, 2) Know students' difficulties in learning opportunity material, 3) Identify causes of difficulties experienced by students in class XII MTS MA AL ITTIHADIYAH Medan Johor academic year 2022 /2023. The data for the study were obtained from samples taken, namely class XII-Tolhah students of 33 students. Data collection techniques were carried out through tests and interviews. Data were analyzed descriptively. The results showed that student learning outcomes were still very low. This is supported because only 14 students (4.2%) out of 33 students completed the opportunity material so that researchers believe that students generally experience learning difficulties in studying opportunity material. The learning difficulties are due to 1) low understanding of the basic concept of opportunity; 2) lack of interest/will; 3) lack of practice to work on probability questions; 4) difficulty analyzing word problems; 5) less meaningful algebra learning.